Legal Aid Services in Malawi - Boyce P. Wanda (Washington University Law Quarterly, 1975)
This Article will acquaint the reader with the organization and operation of legal aid services in Malawi. The discussion of the program will survey the economic, social, and legal context within which the program operates, the constitutional framework and the practical operation of the whole scheme, including the administration of the Legal Aid Department, the recruitment and functioning of the professional staff, and the kind of cases with which the Department deals.
Keywords: Malawi